TEACHER TRAINING: HOW TO MAKING LEARNING PLANS IN KKG CIBAL AND CIBAL BARAT - Ndeot, Felisitas Ica; Palmin, Beata; Jaya, Petrus Redy (STKIP Santu Paulus Ruteng, 2019)
This activity aims to improve the competence of teachers of early childhood teachers pedagogic and professional in the PKG Cibal and Cibal Barat. Teachers as a members of PKG Cibal and Cibal Baratt realized the importance of this activity will be carried out as a form of activity which may increase the ability of teachers which is largely a HIGH-SCHOOL graduate. A learning plan is a means for teachers in designing activities around in the early childhood education. Teachers are expected to design a learning plan in accordance with the characteristics, circumstances, and conditions of early childhood so the learning given ongoing fun and exciting. The methods used in this activity is the method of discussion, mentoring, and training